A timidez na perspectiva da psicologia analítica - Esteves, Ana Letícia (2012)
This study aimed to review the literature on shyness in the perspective of Analytical Psychology. In this process, it was found that this subject is scarcely studied in jungian literature. The shyness s concept adopted was the personality characteristic that is marked by fear of social situations and other people, especially strangers, because the fear of a negative judgment. Thus, it must be configured as an object of study of psychology as it can cause pain and difficulties in one s life that has this attribute. From the bibliography it was found that there was a relationship between shadow and persona with shame. The role of shame is not only to suppress the contents but also to recognize and assimilate these shameful contents that were repressed or projected, which is essential to self-knowledge. Shame is the prompt reaction to the realization that something that does not fit the ideal image of oneself unveiled behind the mask. The individual quest for perfection and a good image of oneself, excludes all that is dark, blocking the process of individuation, which it is premised also integrate what is dark and imperfect. In the book 'Memories, Dreams, Reflections' shyness was the word used to denote what Jung felt when he 'encountered' for the first time with the anima, understood as the unknown and unconscious. The approach to these unconscious contents can generate fear and resistance, feelings that are in agreement with the conception of shyness. However, as these contents have been integrated in conscious it can promote personality growth. The work of Aron relates the shyness to the object of their study, which was the 'high sensitivity' from the perspective of Analytical Psychology. 'Highly sensitive' individuals develop shyness more easily as they experience the same unfavorable environment in a more negative way. The search for internal resources to address the fear of the other, that is unknown, will be beneficial both to overcome shyness and to be open up to new possibilities. It is the psychodynamics between self and other that promotes growth